Incident Laser Power and Concentration Effects on the Fluorescence of DCM Dye in PMMA Polymer - Al-Wattar, Abbas J.; Chiad, Baha T.; Taleb, Ansam J. (Iraqi Journal of Laser, 2007)
Incident laser power and concentration effects on fluorescence emission from DCM dye in PMMA polymer have been investigated. Different concentrations of the dye were used. It was found that the fluorescence intensity increased with increasing of the concentration of the dye, with a red shift. In addition, it was found that the fluorescence intensity increased with the increase of the incident laser power I0.